Modeling the Maturation of Grip Selection Planning and Action Representation: Insights from Typical and Atypical Motor Development - Fuelscher, Ian; Williams, Jacqueline; Wilmut, Kate; Enticott, Peter G.; Hyde, Christian (Frontiers in Psychology, 2016)
We investigated the purported association between developmental changes in grip selection planning and improvements in an individual’s capacity to represent action at an internal level (i.e., motor imagery). Participants were groups of healthy children aged 6-7 years and 8-12 years respectively, while a group of adolescents (13-17 years) and adults (18-34 years) allowed for consideration of childhood development in the broader context of motor maturation. A group of children aged 8-12 years with probable DCD (pDCD) was included as a reference group for atypical motor development. Participants’ proficiency to generate and/or engage internal action representations was inferred from performance on the hand rotation task, a well-validated measure of motor imagery. A grip selection task designed to elicit the end-state comfort (ESC) effect provided a window into the integrity of grip selection planning. Consistent with earlier accounts, the efficiency of grip selection planning followed a non-linear developmental progression in neurotypical individuals. As expected, analysis confirmed that these developmental improvements were predicted by an increased capacity to generate and/or engage internal action representations. The profile of this association remained stable throughout the (typical) developmental spectrum. These findings are consistent with computational accounts of action planning that argue that internal action representations are associated with the expression and development of grip selection planning across typical development. However, no such association was found for our sample of children with pDCD, suggesting that individuals with atypical motor skill may adopt an alternative, sub-optimal strategy to plan their grip selection compared to their same-age control peers.